2003
DOI: 10.1260/030952403322665271
|View full text |Cite
|
Sign up to set email alerts
|

Solidity and Blade Number Effects on a Fixed Pitch, 50 W Horizontal Axis Wind Turbine

Abstract: Experimental studies were conducted on a modified Rutland 500 horizontal axis wind turbine to evaluate numerical implications of solidity and blade number on the aerodynamic performance. Wind tunnel data were acquired on the turbine with flat-plate, constant-chord blade sets and optimum-designed blade sets to compare with theoretical trends, which had indicated that increased solidity and blade number more than conventional 3-bladed designs, would yield larger power coefficients, CP. The data for the flat plat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 6 publications
0
17
0
Order By: Relevance
“…The effects of other parameters to the aerodynamic performance of small turbines, such as rotor solidity and blade number have also been investigated. The numerical and experimental studies [20,21] on a 50W horizontal axis wind turbine show that increasing the solidity leads to increased power coefficient at low tip speed ratios, and an increase in the blade number also increases the maximum Cp, so the solidity or blade number increases can lead to a higher overall system power yield. Study also finds that while using more blades, more torque could be added to help start the turbine, and one of the major problems for the small wind turbines is solved, which is the difficulty to start rotating in low wind speed in built environment because of small torque [7].…”
Section: Optimisation Of Performance Of the Small Wind Turbinementioning
confidence: 99%
“…The effects of other parameters to the aerodynamic performance of small turbines, such as rotor solidity and blade number have also been investigated. The numerical and experimental studies [20,21] on a 50W horizontal axis wind turbine show that increasing the solidity leads to increased power coefficient at low tip speed ratios, and an increase in the blade number also increases the maximum Cp, so the solidity or blade number increases can lead to a higher overall system power yield. Study also finds that while using more blades, more torque could be added to help start the turbine, and one of the major problems for the small wind turbines is solved, which is the difficulty to start rotating in low wind speed in built environment because of small torque [7].…”
Section: Optimisation Of Performance Of the Small Wind Turbinementioning
confidence: 99%
“…al. [19] discussed the effect of the number of blades and the runner solidity for small wind turbines. This work concludes that the optimum design three-blade rotors produced an increase in the experimental power coefficient-Cp as solidity increased, with reduced tip speed ratio (TSR) at the optimum operating point.…”
Section: Introductionmentioning
confidence: 99%
“…al. [19] just change the number of blades in the rotor without making modification in the blade design. In the Glauert theory, the solidity has to be changed for the optimum design geometry, for each different number of blades.…”
Section: Introductionmentioning
confidence: 99%
“…11 HKTs are lift/drag devices similar to wind turbines, and their performance is governed by several non-dimensional quantities: (i) the tip-speed ratio (TSR : k ¼ RX U ), which is defined as ratio of blade tip speed to fluid speed (U) (where R is turbine radius) and X is the rpm; (ii) solidity (r ¼ Bc 2pR ) that is defined as the ratio of the product of the blade chord length (c) and the number of blades (B) to the turbine circumference; and (iii) the chord Reynolds number (Re ¼ qUc=l), where q and l are the density and viscosity of the fluid medium. Over the last decade, the flow-dynamics of wind turbines and HKTs have been investigated using computational fluid dynamics (CFD) 4,12,13 and laboratory scale experiments. [14][15][16][17][18] Blade-element-momentum (BEM) analysis which forms the backbone of wind turbine rotor design can also be used for HKTs design.…”
Section: Introductionmentioning
confidence: 99%
“…Hwang et al 29 investigated the effect of variation of TSR, chord length, number of blades, and the shape of hydrofoil on performance of a variable pitch vertical axis water turbine using both experiments and numerical calculations. Duquette and co-workers 12,13 performed experiments and 2-D numerical analysis to study the effect of number of blades and solidity on the performance of a horizontal axis wind turbine. Their analysis concluded that the range of TSR for maximum C p depends strongly on solidity and weakly on the number of blades.…”
Section: Introductionmentioning
confidence: 99%